2011
DOI: 10.5194/hess-15-1865-2011
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variations in soil moisture and physicochemical properties of a typical semiarid sand-meadow-desert landscape as influenced by land use

Abstract: Abstract.A good understanding of the interrelations between land cover alteration and changes in hydrologic conditions (e.g., soil moisture) as well as soil physicochemical properties (e.g., fine soil particles and nutrients) is crucial for maintaining the fragile hydrologic and environmental conditions of semiarid land, such as the Horqin Sandy Land in China, but is lacking in existing literature. The objectives of this study were to examine: (1) spatio-temporal variations of soil moisture and physicochemical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…Groundwater in the northwest of the study area either flows into the lake at a hydraulic gradient of 0.65‰ to 1.05‰ or to the sink area surrounding sites C2(M) and C2(G) (Figure 2a) at a greater gradient of 1.08‰. This sink probably originated as a result of localized geological conditions such as the patch of higher ground between sites D2 and C3, as shown in Figure 2b, which formed a geological barrier to hinder the southeasterly flow of groundwater [21]. Another possible explanation is that the natural water table surrounding the sink was lowered by agricultural activities (Figure 1a) to such an extent that the groundwater flow direction beyond site C2(M) was reversed.…”
Section: Water Table Spatial Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Groundwater in the northwest of the study area either flows into the lake at a hydraulic gradient of 0.65‰ to 1.05‰ or to the sink area surrounding sites C2(M) and C2(G) (Figure 2a) at a greater gradient of 1.08‰. This sink probably originated as a result of localized geological conditions such as the patch of higher ground between sites D2 and C3, as shown in Figure 2b, which formed a geological barrier to hinder the southeasterly flow of groundwater [21]. Another possible explanation is that the natural water table surrounding the sink was lowered by agricultural activities (Figure 1a) to such an extent that the groundwater flow direction beyond site C2(M) was reversed.…”
Section: Water Table Spatial Patternsmentioning
confidence: 99%
“…In the HSL, surface water is negligible and the vegetation primarily depends on groundwater for survival and development [31][32][33][34]. Duan et al [21] found that the spatio-temporal variation of vegetation in the HSL is dominated by groundwater availability and only slightly influenced by soil physicochemical properties such as soil texture, soil organic content, soil salinity, and plant physiology. Ma et al [35] analyzed the relationship between vegetation ecotypes and groundwater depth in the HSL, and showed that the ranges of water table depth for hygrophyte, mesophyte, mesoxerophyte and xerophyte varied from 0.45 m to 1.66 m, 0.95 m to 2.20 m, 2.20 m to 4.59 m, and 3.45 m to 7.45 m, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These problems are in turn likely to threaten the sustainability of "grassland agriculture," a system of agriculture in which the major emphasis is on grasses, legumes, and other fodder or soil-building crops [19]. The main factors causing degradation are overgrazing, cultivation, overdevelopment, and climate change [16,[20][21][22][23], which have altered the natural hydrology in the area [24] and led to the erosion of approximately 10 to 20 cm of calcic castanozem topsoil [25]. This topsoil is vital for efforts to sustain grasslands because it is loose and has a plentiful supply of humus/organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…Evaporation from bare sandy soils is the core component of the hydrologic cycle (dominated by vertical water movement) in arid/semiarid regions, where any disturbance to the fragile hydrology is likely to trigger land desertification and deteriorate the very sparse vegetation ecosystem [1][2][3][4][5][6][7]. For instance, the 51,700 km 2 Horqin Sandy Land (HSL; 118°35′ to 123°30′ E, 42°41′ to 45°15′ N), one of the most typical sandy lands in the world and historically part of the largest and most characteristic Eurasian grassland [8], has undergone severe desertification in recent decades [9,10]: deserted land has reached 57.8% of the HSL's total area [11].…”
Section: Introductionmentioning
confidence: 99%